2007
DOI: 10.1523/jneurosci.2513-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Timing-Dependent Plasticity of Neocortical Excitatory Synapses on Inhibitory Interneurons Depends on Target Cell Type

Abstract: Repetitive correlated spiking can induce long-term potentiation (LTP) and long-term depression (LTD) of many excitatory synapses on glutamatergic neurons, in a manner that depends on the timing of presynaptic and postsynaptic spiking. However, it is mostly unknown whether and how such spike-timing-dependent plasticity (STDP) operates at neocortical excitatory synapses on inhibitory interneurons, which have diverse physiological and morphological characteristics. In this study, we found that these synapses exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(173 citation statements)
references
References 58 publications
10
161
2
Order By: Relevance
“…1B) could be driven by spike-timing-dependent plasticity in FS interneurons, as postulated previously (10). Coincident (卤10 ms) firing between presynaptic principal and postsynaptic FS neurons within the extragranular cortex causes synaptic depression in vitro, regardless of which of the neurons fires first (19). Accordingly, the more active an excitatory input is, the greater the likelihood of both coincident FS postsynaptic activity and synaptic depression in vivo.…”
Section: Md-induced Response Depression In Fs Interneurons Is Consistentmentioning
confidence: 61%
“…1B) could be driven by spike-timing-dependent plasticity in FS interneurons, as postulated previously (10). Coincident (卤10 ms) firing between presynaptic principal and postsynaptic FS neurons within the extragranular cortex causes synaptic depression in vitro, regardless of which of the neurons fires first (19). Accordingly, the more active an excitatory input is, the greater the likelihood of both coincident FS postsynaptic activity and synaptic depression in vivo.…”
Section: Md-induced Response Depression In Fs Interneurons Is Consistentmentioning
confidence: 61%
“…Reduced neuronal activity is likely resulting from a depression of the excitatory inputs. Excitatory synapses at FS inhibitory interneurons largely follow an anti-Hebbian rule of synaptic plasticity (for review, see Kullmann and Lamsa, 2007), showing synaptic LTD after prolonged high-frequency input activity and following repeated application of a spike-time-dependent plasticity stimulation protocol usually inducing LTP in excitatory neurons (Lu et al, 2007). Moreover, brain-derived neurotrophic factor (BDNF) released during high-frequency input activity (Hartmann et al, 2002) promotes synaptic depression at excitatory inputs to PVpositive neurons (Jiang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since c-Fos expression appears to reflect the activity level but not the activity pattern of neurons, direct measurement of the activity pattern of callosal projection neurons, by electrophysiological recordings, for example, may be required to assess their rhythmic activity. A previous study has shown that the activity of SST-positive cells appears to be blocked by NMDA receptor antagonists more easily than the activity of PV-positive interneurons (Lu et al, 2007) Mechanisms by which MGE cell transplantation prevents PCP-induced behavioral deficits It remains unclear how MGE cell transplantation prevented PCPinduced behavioral deficits. Although we found that the preventive effect of MGE cell transplantation on the PCP-induced behavioral deficits was accompanied by an increase in the c-Fos level in the mPFC (Fig.…”
Section: Mge Cell Transplantation Did Not Cause Behavioral Effects Inmentioning
confidence: 99%